2017
DOI: 10.1186/s12887-016-0773-9
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of food allergies: a survey of pediatricians in Kuwait

Abstract: BackgroundEarly diagnosis of food allergies (FA) is important for a favorable prognosis. This study aimed to determine the level of awareness of FA among pediatricians in Kuwait.MethodA 43-item self-administered questionnaire was designed and distributed to pediatricians working at 4 government hospitals in Kuwait.ResultsA total of 140 pediatricians completed the questionnaire, with a participation rate of 51.1% (81 males and 59 females). The mean age of participants was 40.81 years, and the mean number of yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…[9,10] Interestingly weaknesses in knowledge about diagnostic tests seems like a common problem between primary care physicians, as similar findings were reported by both studies in the US and Turkey. [9,10] Weaknesses in treatment and prevention is partially in line with present research, Al-Herz et al [22 national study on pediatricians' awareness about FA recorded fair pediatricians' knowledge about FA treatment, 77% but low knowledge levels in prevention, 42%. Physicians in Kuwait just like those in Turkey longing for training about FA.…”
Section: Discussionsupporting
confidence: 87%
“…[9,10] Interestingly weaknesses in knowledge about diagnostic tests seems like a common problem between primary care physicians, as similar findings were reported by both studies in the US and Turkey. [9,10] Weaknesses in treatment and prevention is partially in line with present research, Al-Herz et al [22 national study on pediatricians' awareness about FA recorded fair pediatricians' knowledge about FA treatment, 77% but low knowledge levels in prevention, 42%. Physicians in Kuwait just like those in Turkey longing for training about FA.…”
Section: Discussionsupporting
confidence: 87%
“…The questionnaire was developed and adapted by the researcher based on Al-herz et al, (2017) and Gupta et al, (2009). The survey asked about the respondents' profile, general food allergy knowledge and the types of intervention that can improve their knowledge.…”
Section: Methodsmentioning
confidence: 99%
“…This raises the question of whether food providers have the proper knowledge to prevent incidence of food allergic reaction. Previous studies have found that one of the major factors that contribute to the incidence of food allergic reaction is the lack of knowledge among the public as well school nurses, hospitality staff and pediatricians (Din, Rashid &Ramli 2015 andAlherz, Husain, Alkhabaz, Moussa, &Al-refaee 2017). Therefore, determining the level of food allergy knowledge is fundamental before creating any intervention.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 26 In the Middle East, several studies aimed to examine the prevalence of food allergies and identify the most common food allergens among different populations. 2 , 3 , 9 , 19 …”
Section: Introductionmentioning
confidence: 99%